ALTERNATIVE FORMS OF EDUCATION IN OHS - DEPEŠOVÁ, Jana; TOMKOVÁ, Viera (Trends in education, 2013)
Study program "Occupational Health and Safety"gives very important capabilities and skills for graduate students. Because of this program, students are able to work in labor market as safety engineer, inspector, safety inspector or do professions for the government and state administration. Just focus on training qualified students of OHS, it requires to put, among others, alternative forms of knowledge acquisition into study program.
Keywords: education; occupational health and safety; alternative forms